Analisis Potensi Lestari Sumberdaya Perikanan Tuna Longline di Kabupaten Cilacap, Jawa Tengah - Onolawe Prima Sibagariang; Fauziyah .; Fitri Agustriani (UNIVERSITAS SRIWIJAYA, 2011)
Maximum sustainable yield of tuna long line fisheries in Cilacap district was motivated by the large potential of tuna fisheries resources which are owned 26% of the total fish production in Cilacap, or 1225 tons per year. The aim of this research is to calculate maximum sustainable yield (MSY) value from tuna fisheries resources using statistic method. Calculation results obtained using the Schaefer model, maximum sustainable yields (MSY) of 1439.86 tons / year and the optimum effort was 155 units / year. Tuna fisheries resources utilities in Cilacap of 85.12%, Its mean that status of utilization tuna fisheries resources is over fishing. Keywords: Cilacap District, MSY, Schaefer, Tuna fisheries ABSTRAK Analisis potensi lestari perikanan tuna longline di Kabupaten Cilacap dilatarbelakangi oleh besarnya potensi sumberdaya perikanan tuna yang dimiliki yaitu 26 % dari seluruh jumlah produksi ikan di Cilacap atau 1225 ton per tahun.Â Tujuan penelitian ini untuk menghitung nilai potensi lestari sumberdaya perikanan tuna menggunakan metode statistika sehingga pengembangan perikanan tuna dapat dilakukan secara optimal.Â Hasil perhitungan dengan menggunakan model Schaefer didapatkan potensi lestari (MSY) sebesar 1439,86 ton/tahun dan upaya optimumnya adalah 155 unit/tahun. Adapun tingkat pemanfaatan sumberdaya ikan tuna di perairan Cilacap sebesar 85,12 %, dapat dikatakan status pemanfaatannya dalam kondisi tangkap lebih (overfishing) . Kata kunci : Cilacap, MSY, Schaefer, Perikanan tuna